The Development of a Commode Pan for a Hygiene Chair - Möttus,David (2025)
This thesis project was completed in collaboration with Arjo, a MedTech company headquartered in Malmö, Sweden. Arjo’s product offering is largely centered around providing healthier outcomes for individuals with limited mobility and includes products for patient transfer, hygiene, disinfection, etc. One product type which is central to Arjo’s mission is the hygiene chair. This type of product is used for a variety of activities such as showering, toileting, and other hygiene activities. A common accessory product to hygiene chairs is the commode pan. While not critical components, their presence and ease of use significantly impacts caregivers’ work. Commode pans have traditionally been attached to hygiene chairs via rails. This attachment method, although simple, implies hygiene issues as well as a pinching risk of the caretaker’s genitalia. During the summer of 2024 a new commode pan concept was developed to address the issues related to hygiene and patient safety. While successful in mitigating the highlighted issues, this concept did imply new limitations. This thesis project, therefore, aims to refine the commode pan concept with a focus on usability, ergonomics, sustainability, and producibility. The project was completed in a methodical manner structured around the Double Diamond Design Process. The theoretical framework was established based on the defined limitation categories. This theoretical framework was utilized during the discover stage in order to efficiently evaluate the initial concept’s limitations. The initial concept was also evaluated based on user testing data and interviews with engineers at Arjo. Once the limitations had been discovered it was possible to translate them into actionable areas of refinement, enabling the project to efficiently define the needs, metrics, and target specifications. During the develop and deliver stages of the Double Diamond Design Process commode pan concepts were developed, evaluated, selected, and iterated upon until the final commode pan concept was defined. Although there are several areas of future work which need to be completed before the final commode pan concept becomes entirely viable, it is believed that the developed concept largely solves the initial concept’s limitations relating to usability, ergonomics, sustainability, and producibility.
Keywords: Ergonomics; Design for Injection Molding; Modular Prototyping; Commode Pans; Hygiene